PERSEPSI PEGAWAI TENTANG GAYA KEPEMIMPINAN ATASAN LANGSUNG DI DINAS SOSIAL DAN TENAGA KERJA KOTA PADANG - PINTA UMMUL HUSNA RAMADHANI (Jurnal Bahana Manajemen Pendidikan, 2016)
This research is motivated from observations of the author in Dinas Sosial dan Tenaga Kerja Kota Padang.which shows lack of good leadership style direct supervisor at the Dinas Sosial dan Tenaga Kerja Kota Padang. The purpose of this study was to obtain information about employees on leadership styles Perspsi Direct Supervisors at the Dinas Sosial dan Tenaga Kerja Kota Padang: 1) Implementation of tasks by giving instructions to subordinates, carrying out surveillance, giving confidence to the employee in performing its duties and focusing attention on the implementation of tasks, 2) The relationship of humanity with the way the leadership to motivate employees to work, leadership involves employees in decision and leadership to develop family relationships. Research question posed is how the employee perception of leadership style direct supervisor at the Dinas Sosial dan Tenaga Kerja Kota Padang Oriented tasks and human relations.